Growth Performance Of Turkeys Under Field Condition - Thomas, K.Shibi; Reetha , T.Lurthu; Babu , M. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The modern domesticated turkey descends from the wild turkey (Meleagris gallopavo) which was domesticated years before in Mexico. Turkey, native of North America, is an important poultry species reared for meat production. Turkey is easy to rise with similar management as chicken and can also be reared in free-range system (Khaddakar, 2001). Turkey farming is an evolving sector which is playing a significant role in augmenting the economic and nutritional status of the farming community. They are reared for meat among the domestic poultry species (Rajendranet al., 2012). Turkeys are better foragers than chickens, and can digest fibre better than chicken. Turkeys are able to derive more energy from low energy diets as compared to chicken and turkeys diets need to have a narrower energy to protein ratio (Tyagi, 2001). The present study was conducted to study the growth performance of poults (Broad Breasted White Turkey) maintained in a semi-intensive manner in a turkey farm at Egrimangalam, Tiruchirapalli District.